1998
DOI: 10.1056/nejm199802053380601
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Pneumothorax and Other Air Leaks to Mortality in the Acute Respiratory Distress Syndrome

Abstract: In patients with sepsis-induced acute respiratory distress syndrome who were receiving mechanical ventilation with conventional pressures and volumes, there were no significant correlations between high ventilatory pressures or volumes and the development of pneumothorax or other air leaks. Pneumothorax or other air leaks were not associated with a significantly increased mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(78 citation statements)
references
References 37 publications
5
66
2
2
Order By: Relevance
“…A number of studies have concluded that the incidence of barotrauma does not relate to ventilator mode. [212223]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have concluded that the incidence of barotrauma does not relate to ventilator mode. [212223]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation of SPM includes retrosternal chest pain with radiation to the back in 90% of cases. Persistent cough is described in 42%; dysphonia, throat or jaw pain in up to 25%21 and dyspnoea in approximately 8% of cases 21. Physical examination reveals subcutaneous air in 73% of reported cases 22.…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination reveals subcutaneous air in 73% of reported cases 22. Hamman's sign, although less common, is pathognomic of pneumomediastinum 21. A low-grade fever may be present and is thought to be a result of cytokine release 23.…”
Section: Discussionmentioning
confidence: 99%
“…Although one study showed that the incidence of pneumothorax decreased after implementation of protective lung strategies [27] , several recent studies comparing low tidal volume with conventional ventilation in ARDS failed to demonstrate any reduction in barotrauma when low tidal volumes were used [41][42][43] . Previous literature showed the incidence of barotrauma did not relate to the ventilatory settings [22,31,41,44] but a low compliance was associated with a high incidence of barotrauma, which suggested that barotrauma has been more related to the underlying process than the ventilatory setting [40] .…”
Section: Factors For Prmvmentioning
confidence: 99%
“…Pneumothorax was found to be an independent predictor of mortality during mechanical ventilation [18] and was associated with a significant increase in the ICU length of stay, hospital stay and mortality in all mechanically ventilated patients [3] . The mortality rates are high, ranging from 46% to 77% if barotrauma is a complication of mechanical ventilation [2,3,14,15,[19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%